2023
DOI: 10.3389/fenrg.2022.1076050
|View full text |Cite
|
Sign up to set email alerts
|

China’s green finance and total factor energy efficiency

Abstract: Based on data on 280 prefecture-level cities from 2008 to 2019, this study uses a difference-in-difference (DID) model to first analyze the impact of China’s green finance pilot policy (GFPP) on total factor energy efficiency (TFEE) and then further investigate the mediating and heterogeneous effects of GFPP. Results indicate that first, GFPP effectively improves TFEE, and the robustness tests show that the estimation results are reliable. Second, GFPP mainly improves TFEE by promoting industrial structure opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The authors focused on studies on sustainable investment options, analyzed how environmental, social, and governance aspects are incorporated into financial decision-making, and evaluated how sustainability affects financial performance. Researchers are expected to advance ethical and sustainable financial practices and help the world accomplish its sustainability goals by studying sustainability within the context of green finance [5,25,43,46,59,73,77,90,91,94,104,109,138,161,163,165,167,171].…”
Section: Discussionmentioning
confidence: 99%
“…The authors focused on studies on sustainable investment options, analyzed how environmental, social, and governance aspects are incorporated into financial decision-making, and evaluated how sustainability affects financial performance. Researchers are expected to advance ethical and sustainable financial practices and help the world accomplish its sustainability goals by studying sustainability within the context of green finance [5,25,43,46,59,73,77,90,91,94,104,109,138,161,163,165,167,171].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese government has been actively advocating the establishment of a green financial system and initiated the Green Finance Reform and Innovation Pilot Area (GFRI) in 2017. Numerous studies have substantiated the significant impact of the GFRI on energy efficiency, green innovation, the costs of debt financing, and the level of financialization [ [37] , [38] , [39] , [40] , [41] , [42] ]. Core policy measures emphasize the development of diverse financing instruments, including green credit and green bonds, to expand the financing channels for green projects [ 39 , 41 ].…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…The DID model has become a common method for evaluating the implementation effect of a policy [33,34]. When evaluating the implementation effect of China's green finance policy, existing research widely uses the DID method for regression analysis [8][9][10]. To describe the policy impact and effectively overcome the related endogenous problems, we use the DID methodology to analyze the effect of GFRI on GI, take the pilot and nonpilot enterprises as the treated and control groups, respectively, and add other variables that have an impact on the GI effect.…”
Section: Did Modelmentioning
confidence: 99%
“…One important policy is the implementation of the GFRI in 2017. Extensive research has shown that this GFRI significantly impacts energy efficiency, green innovation, debt financing costs, and financialization level [6][7][8][9][10][11]. The core measures of the policy include developing diversified financing tools such as green credit, green bonds, and green insurance to expand financing channels for green projects.…”
Section: Introductionmentioning
confidence: 99%